Confirmatory Factor Analysis of Circular Economy Practices (5r Framework) at Andri 99 Leather Garut - Ade Nugraha; Rizky Rahayu; Mira Nur Aeni; Suli Handayani; Hilman Rismanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This research aims For verify structure factor circular economy practices based on the 5R framework (reduce, reuse, recycle, recover, and redesign) in industry skin scale small Andri 99 Leather Garut. Although circular economy concept has Lots being discussed , still little empirical evidence to test relatedness fifth 5R principles in general simultaneously in context industry small companies that use production processes traditional . This research applies approach quantitative with the Confirmatory Factor Analysis (CFA) method for determine whether the implementation of 5R creates One integrated or multidimensional construct . Data obtained through survey to all over craftsmen who play a direct role in activities operational as the population involved completely . The results of the analysis show that the data is valid For processed further (KMO = 0.866; value Bartlett's Test significance = 0.000) and all 5R indicators have mark high loading factor (0.773–0.900) on one factor main with an eigenvalue of 3.633 which is capable of explained 72.65% of the total variance . This finding confirms that Circular economic practices based on 5R in leather SMEs scale small is unidimensional and integrated . This research provides contribution empirical in measuring the circular economy in the MSME sector as well as implications practical For development policies and assistance sustainability industry small based​ craft